Effectiveness of a comprehensive oral management protocol for the prevention of severe oral mucositis in patients receiving radiotherapy with or without chemotherapy for oral cancer: a multicentre, phase II, randomized controlled trial. Issue 7 (July 2019) - Kawashita, Y.; Koyama, Y.; Kurita, H.; Otsuru, M.; Ota, Y.; Okura, M.; Horie, A.; Sekiya, H.; Umeda, M.
Abstract: The aim of this phase II, multicentre, randomized controlled trial was to evaluate the effectiveness of a comprehensive oral management protocol for the prevention of severe oral mucositis in patients with oral cancer receiving radiotherapy alone or chemoradiotherapy. In total, 124 patients with oral cancer were enrolled from five institutions. Of these, 37 patients undergoing radiotherapy were randomly divided into an intervention group ( n = 18) and a control group ( n = 19). The remaining 87 patients, who were undergoing chemoradiotherapy, were also randomized into an intervention group ( n = 42) and a control group ( n = 45). During radiotherapy, patients in the control group received only oral care, while those in the intervention group additionally received spacers to cover the entire dentition, pilocarpine hydrochloride, and topical dexamethasone ointment for oral mucositis. The primary endpoint was the incidence of severe oral mucositis. The intervention was significantly associated with a decreased incidence of severe oral mucositis in patients receiving radiotherapy alone ( P = 0.046), but not in those receiving chemoradiotherapy ( P = 0.815). These findings suggest that an oral management protocol can prevent severe oral mucositis in patients with oral cancer undergoing radiotherapy without concurrent chemotherapy.